PENGARUH DIVIDEND POLICY DAN LEVERAGE TERHADAP PILIHAN KEBIJAKAN AKUNTANSI UNTUK ASET TAK BERWUJUD (Studi Empiris Terhadap Perusahaan Teknologi yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2023) - Febiyanti Febiyanti; R. R. Sri Handayani (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of dividend policy and leverage on the choice of accounting policy for intangible assets in technology companies listed on the Indonesia Stock Exchange for the period 2019–2023. Using the agency theory type III framework, this research highlights the horizontal conflict between shareholders and creditors, as well as the potential for opportunistic behavior by managers in responding to pressures from both parties through financial reporting decisions. The study employs a documentation method with a total of 157 firm-year observations, selected through purposive judgment sampling. Dividend policy is measured using the dividend payout ratio, while leverage is proxied by the debt to asset ratio (DAR). The accounting policy choice is measured using a revenue strategy index based on five key accounting treatments for intangible assets. The data is analyzed using panel data regression models.The results show that dividend policy has a positive and significant effect on the choice of accounting policy for intangible assets, indicating that firms with higher dividend payouts tend to adopt aggressive accounting policies to increase reported income. Conversely, leverage measured by DAR shows a negative and significant effect, suggesting that firms with higher debt proportions tend to adopt more conservative accounting policies for intangible assets in order to maintain creditor trust. These findings suggest that external pressure from creditors can serve as a disciplinary mechanism that limits managerial discretion in pursuing opportunistic reporting behavior. Overall, the study emphasizes that accounting policy choices are shaped not only by shareholder interests but also by external governance forces stemming from a company’s financing structure.